2016
DOI: 10.1007/s00234-016-1729-3
|View full text |Cite
|
Sign up to set email alerts
|

Wall enhancement on high-resolution magnetic resonance imaging may predict an unsteady state of an intracranial saccular aneurysm

Abstract: Aneurysm wall enhancement on HRMRI might be a sign of inflammatory change. Symptomatic aneurysms exhibited wall enhancement on HRMRI. Wall enhancement had a high consistent correlation of symptomatic aneurysms. Therefore, wall enhancement on HRMRI might predict an unsteady state of an intracranial saccular aneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
79
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 20 publications
1
79
0
Order By: Relevance
“…5,9 Hu et al 5 found evidence of inflammation of the aneurysm wall through pathological studies and proved that aneurysm wall enhancement on HRMRI is highly consistent with pathological changes of inflammation. According to a report by Iihara et al 6 regarding resection of a VBDA with a huge IMH, pathological evidence of inflammatory cell infiltration was present in the IMH.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…5,9 Hu et al 5 found evidence of inflammation of the aneurysm wall through pathological studies and proved that aneurysm wall enhancement on HRMRI is highly consistent with pathological changes of inflammation. According to a report by Iihara et al 6 regarding resection of a VBDA with a huge IMH, pathological evidence of inflammatory cell infiltration was present in the IMH.…”
Section: Discussionmentioning
confidence: 95%
“…4,15 Wall enhancement of a saccular aneurysm on HRMRI is a proven sign of inflammatory change and might predict an unsteady state of an intracranial saccular aneurysm. 5,9 However, few studies have focused on wall enhancement of VBDAs. We hypothesized that wall enhancement might also predict an unsteady state of a VBDA as well as its progression after reconstructive EVT.…”
mentioning
confidence: 99%
“…Intracranial vessel wall imaging was initially developed to aid in the diagnosis of CNS angiitis; subsequently, it was used for intracranial atherosclerosis, Moyamoya disease and intracranial aneurysms 3. Several papers have reported partial or circumferential wall enhancement in ruptured aneurysms but also in aneurysms exerting mass effect, partial thrombosis and evolving size/morphology 2 3.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers have reported partial or circumferential wall enhancement in ruptured aneurysms but also in aneurysms exerting mass effect, partial thrombosis and evolving size/morphology 2 3. In all situations, enhancement is considered to be a sign of wall inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation